2017
DOI: 10.1021/acs.jpcb.7b07972
|View full text |Cite
|
Sign up to set email alerts
|

Multispectroscopic and Theoretical Exploration of the Comparative Binding Aspects of Bioflavonoid Fisetin with Triple- and Double-Helical Forms of RNA

Abstract: The interactions of RNA triplex (U.A*U) and duplex (A.U) with naturally occurring flavonoid fisetin (FTN) have been examined at pH 7.0 using various spectroscopic, viscometric, and theoretical studies. Experimental observations showed that the ligand binds with both double- and triple-helical forms of RNA, although the binding affinity is greater for the triplex structure (5.94 × 10 M) compared to that for the duplex counterpart (1.0 × 10 M). Thermal melting experiments revealed that the Hoogsteen base-paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…As mentioned above (see Section 3.3), riboswitches are the best example in nature of a small molecule engaged with a triple helix. In a non‐natural context, more than a dozen small molecules are known to preferentially bind to RNA triple helices over their double helix counterparts or can induce triplex formation: Berberine and analogs (Bhowmik, Das, Hossain, Haq, & Suresh Kumar, 2012; Das, Kumar, Ray, & Maiti, 2003; Sinha & Kumar, 2009), berenil (Pilch, Kirolos, & Breslauer, 1995), coralyne (Sinha & Kumar, 2009), fisetin (Bhuiya, Haque, Goswami, & Das, 2017), luteolin (Tiwari, Haque, Bhuiya, & Das, 2017), neomycin (Arya, Coffee Jr., Willis, & Abramovitch, 2001), palmatine (Sinha & Kumar, 2009), quercetin (Pradhan, Bhuiya, Haque, & Das, 2018), ruthenium(II) complexes (X. J. He & Tan, 2014), sanguinarine (Das et al, 2003) and a benzo[f]quino[3,4‐b]quinoxaline derivative conjugated to neomycin (Arya, Xue, & Tennant, 2003; Figure 7a).…”
Section: Discovering Rna Triple Helicesmentioning
confidence: 99%
“…As mentioned above (see Section 3.3), riboswitches are the best example in nature of a small molecule engaged with a triple helix. In a non‐natural context, more than a dozen small molecules are known to preferentially bind to RNA triple helices over their double helix counterparts or can induce triplex formation: Berberine and analogs (Bhowmik, Das, Hossain, Haq, & Suresh Kumar, 2012; Das, Kumar, Ray, & Maiti, 2003; Sinha & Kumar, 2009), berenil (Pilch, Kirolos, & Breslauer, 1995), coralyne (Sinha & Kumar, 2009), fisetin (Bhuiya, Haque, Goswami, & Das, 2017), luteolin (Tiwari, Haque, Bhuiya, & Das, 2017), neomycin (Arya, Coffee Jr., Willis, & Abramovitch, 2001), palmatine (Sinha & Kumar, 2009), quercetin (Pradhan, Bhuiya, Haque, & Das, 2018), ruthenium(II) complexes (X. J. He & Tan, 2014), sanguinarine (Das et al, 2003) and a benzo[f]quino[3,4‐b]quinoxaline derivative conjugated to neomycin (Arya, Xue, & Tennant, 2003; Figure 7a).…”
Section: Discovering Rna Triple Helicesmentioning
confidence: 99%
“…14−20 Universally, the ESIPT reaction takes place along with the four-level photocycle, i.e., absorption → ESIPT → emission → ground-state intramolecular PT (GSIPT). The great difference of charge arrangement between the phototautomers in ESIPT process leads to the result that ESIPT fluorophores possess peculiar photophysical properties, such as the prominent Stokes shift, 21 dual fluorescence, 22 fastest chemical reaction, 23 and so on. 24,25 Subsequently, these properties trigger crucial applications such as molecular switches, 26 light-emitting diodes, 27 fluorescence imaging, 28 and the like 29−34 in organic new materials and devices.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen bond (HB), as one of the remarkable weak interactions, is generally deemed to play a pivotal role in physical, chemical, and biological processes, such as water solution, , DNA double-strand, , α-helix, , pharmacophore, , and so forth. In recent decades, as the excited-state has been understood in depth, it is confirmed that the HB can enable excited-state intramolecular proton transfer (ESIPT), which gives rise to the production of tautomer with the different electronic construction from the initial excited form. Universally, the ESIPT reaction takes place along with the four-level photocycle, i.e., absorption → ESIPT → emission → ground-state intramolecular PT (GSIPT). The great difference of charge arrangement between the phototautomers in ESIPT process leads to the result that ESIPT fluorophores possess peculiar photophysical properties, such as the prominent Stokes shift, dual fluorescence, fastest chemical reaction, and so on. , Subsequently, these properties trigger crucial applications such as molecular switches, light-emitting diodes, fluorescence imaging, and the like in organic new materials and devices. Consequently, the ESIPT behaviors have been probed deeply from the experimental and theoretical points of view in order to create more valuable compounds.…”
Section: Introductionmentioning
confidence: 99%